2009
DOI: 10.1002/asna.200811136
|View full text |Cite
|
Sign up to set email alerts
|

The chromospherically active binary star EI Eridani: II. Long‐term Doppler imaging

Abstract: Data from 11 years of continuous spectroscopic observations of the active RS CVn-type binary star EI Eridani -gained at NSO/McMath-Pierce, KPNO/Coudé Feed and during the MUSICOS 98 campaign -were used to obtain 34 Doppler maps in three spectroscopic lines for 32 epochs, 28 of which are independent of each other. Various parameters are extracted from our Doppler maps: average temperature, fractional spottedness, and longitudinal and latitudinal spot-occurrence functions. We find that none of these parameters sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Doppler images based on observation with larger phase gaps than this have been published before, e.g. in the studies of II Peg (Berdyugina et al 1998), EI Eri (Washuettl et al 2009), and HD 171488 (Jeffers et al 2011). The largest phase gap in the observations from 2006 corresponds to roughly 160…”
Section: Spectroscopic Observations With Sofinmentioning
confidence: 68%
“…Doppler images based on observation with larger phase gaps than this have been published before, e.g. in the studies of II Peg (Berdyugina et al 1998), EI Eri (Washuettl et al 2009), and HD 171488 (Jeffers et al 2011). The largest phase gap in the observations from 2006 corresponds to roughly 160…”
Section: Spectroscopic Observations With Sofinmentioning
confidence: 68%
“…Long term photometric monitoring of EI Eri seemed to indicate a ∼11 yr brightness cycle that was conjectured to be an analog of the solar activity cycle (Oláh & Strassmeier 2002), but unlike the sun, long term Doppler imaging of EI Eri by Washuettl et al (2009b) shows little variability of its cool starspots over 11 yr. As for the hot corona, Osten et al (2002) observed EI Eri with ASCA (and EUVE) and fitted its spectrum with a 2T model of kT = 0.72 keV and 2.2 keV, but the abundances could not be tightly constrained with ASCA. The XMM-Newton CCD spectra of a short flare on EI Eri on 2009-08-06 during the present campaign was analyzed by Pandey & Singh (2012), who suggested the flare originated from a loop the size of ∼R * (primary), which is about a tenth of the binary separation distance.…”
Section: Ei Erimentioning
confidence: 99%